Penerapan Full Day School di Sekolah Islam Terpadu terhadap Motivasi Belajar Siswa (Studi Kasus di SD IT, SMP IT dan SMK IT Rejang Lebong) - H.M. Taufik Amrillah; Agus Riyan Oktori; Yosi Yulizah (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
The full day school program, also known as full day school, was first established through Ministerial Regulation no. 23 of 2017. Considering that this program has only been implemented for a few years, there are several interesting things to research both in terms of implementation, student learning outcomes and student motivation in learning. The method used in this research is the Mix Method, which is a quantitative method with qualitative methods that are used together in a research activity, so that data is obtained that is more comprehensive, valid, reliable and objective in describing the implementation of the full day school policy in schools based on Integrated Islam in Rejang Lebong Curup Regency and its influence on student learning motivation. Research findings confirm that there are five dimensions which include a number of indicators of the factors determining the level of student learning motivation. These include 1) Perseverance in learning, which includes several indicators such as encouragement to attend school, attend PBM in class, and study outside school hours; 2) Tenacious in facing difficulties, making efforts to overcome the difficulties encountered; 3) Interest and sharp attention in learning, enthusiasm for following PBM; 4) Achieve in learning with the desire to excel and the drive to obtain good results; 5) Be independent in learning to complete assignments or homework and take advantage of opportunities outside of class hours at school.